STUDENTS' PROBLEMS IN WRITING ANALYTICAL EXPOSITION TEXT IN EFL CLASSROOM CONTEXT - Lala Nurlatifah; Fazri Nur Yusuf (University of Kuningan, 2022)
Writing is perceived as the most challenging skill among other productive skills in English language learning. This preliminary study aims at revealing problems encountered by secondary EFL students writing analytical exposition. Employing students' writing and interviews in qualitative manner, 25 second-year EFL secondary students in Bandung, Indonesia, were purposefully involved. Result indicated that students encountered three major problems in writing their analytical exposition; cognitive, linguistic, and psychological problems. Cognitively, most students had limited knowledge of the topic, problems with the structure of the text, the mechanism for capitalization, punctuation, and spelling, and difficulties in sharing ideas due to limited English vocabulary. Linguistically, students frequently encounter the two most challenging areas: vocabulary and grammar. Psychologically, students often found difficulties starting writing, lack of interest, laziness, and confusion in deciding sentence structures. Further discussion of the results is recommended to take into consideration to determine the appropriate treatment for the follow-up research.